STUDI KASUS PERENCANAAN KOMBINASI SISTEM PRACETAK DENGAN ISOLASI DASAR PADA APARTEMEN PANCORAN RIVERSIDE II - Martinus Nifotuho Fau; Hari Nugraha Nurjaman (UKI Press, 2023)
The development and application of high-performance precast systems with prescriptive planning concepts and regimes, it is fully produced locally in Indonesia. However, precast systems that use base isolation, especially in high-rise buildings, need a deeper study to determine the overall behavior and performance of the building. The purpose of this study is to plan a structure that uses a combination of precast and base isolation systems with a case study of a high-rise building, namely the Pancoran Riverside II Apartment, which is located in Jakarta and consists of a tower area of 32 floors and a podium area of 6 floors. The use of base isolation can also shift the period of the structure to be larger, so that a smaller base shear can be obtained, but because the tower area of this building is quite high (121.6 m), the period of the structure is large enough so that the effect of shifting the period of the structure is not very effective in the area. tower, while the podium area (19.2 m) can still take advantage of this decrease in base shear.